Pengaruh Risiko Bank Terhadap Profitabilitas (Studi Kasus Sektor Perbankan Yang Terdaftar di Bursa Efek Indonesia Periode 2015-2020) - Hermawan, Bambang; Ismail, Tubagus; Ichwanudin, Wawan (Faculty of Economics and Business - Universitas Sultan Ageng Tirtaysa, 2021)
This study aims to examine and determine the effect of bank risk on profitability in the banking sector listed on the Indonesia Stock Exchange for the 2015-2020 period. Bank risk includes credit risk, market risk, operational risk, liquidity risk, capital risk and bankruptcy risk. The total sample is 36 banks. This study uses panel data regression analysis. The results showed that credit risk and operational risk had a significant negative effect on profitability. Market risk, capital risk and bankruptcy risk have a significant positive effect on profitability. Meanwhile, liquidity risk has no significant effect on profitability. Simultaneously, all bank risks have a significant positive effect on profitability together. The level of determination is 96.94%, while 3.06% is influenced by other variables notincluded in this study